Desa Wisata Budaya Wayang Kulit Jawa Sebagai DestinasiWisata Minat Khusus dan Komoditas Pariwisata Indonesia - Priyanto, Priyanto (UI Scholars Hub, 2017)
The changing trend of tourism from conventional tourism to special interest tourism encourages the growth and development of several cultural tourism villages in Indonesia. Amid various challenges, the existence of Javanese wayang kulit tourism village continues to clean up to be able to exist. This study aims to explore the potential of wayang kulit cultural tourism village as a tourist destination of special interest and tourism commodity of Indonesia case study of Wayang Kulit Pucung Tourism Village, Bantul Regency (DIY), Wayang Kulit Gendeng Tourism Village, Bantul Regency (DIY) and Wayang Tourism Village, Kepuhsari, Wonogiri Regency (Central Java) Through the qualitative research method, it is found the result of research shows that in general the Javanese wayang kulit tourism village as a special interest tourism destination is very potential to be developed further and its potential is quite a lot.This research suggested that the potential of cultural tourism village Javanese wayang kulit can be more optimal, it takes active participation from various parties, especially the local culture village community to be able to develop the potential of cultural tourism village